Consumer Behavior in Selecting Fuel (BBM) From Gas Stations and Retail Fuel in Mimika Regency - Hillary Gabriela Nussy; Ancelina Mayau; Selviana Edoway; Rulan L. Manduapessy (Jurnal Ekonomi Balance, 2025)
This study investigates consumer behavior in selecting between official gas station (SPBU) fuel and retail fuel sold informally by local communities in Mimika Regency, Indonesia. Informal fuel trading has become a significant socio-economic phenomenon influencing price stability and transportation sector dynamics in Timika. The research aims to identify key factors shaping consumer preferences, assess the impact of retail fuel practices on price stability and transportation economics, and evaluate the effectiveness of existing regulatory enforcement. Employing a descriptive qualitative approach, data were collected through in-depth interviews with retail fuel sellers, public transport drivers, and users of transport services, combined with field observations at major retail fuel points such as Hasanuddin Street, SP2, and Timika Central Market. Secondary data from relevant government agencies and media sources supported the analysis. The findings reveal that despite the sufficient availability of SPBU facilities, many consumers prefer retail fuel due to accessibility, time efficiency, and perceived affordability. During 2022–2025, retail fuel sales reached approximately 13,719 KL for Pertalite and 6,405 KL for Pertamax, reflecting a large-scale informal market. This activity caused consumer-level fuel price fluctuations ranging from IDR 10,000 to 15,000 per liter, generating instability in transportation costs and fare systems. Although 27 enforcement operations were conducted during 2023–2024, implementation remains constrained by structural and operational barriers. The study concludes that addressing this issue requires strengthening regulatory enforcement, improving formal distribution systems, and expanding SPBU infrastructure aligned with local consumer behavior.